Structure of the Anthrax Protective Antigen D425A Dominant Negative Mutant Reveals a Stalled Intermediate State of Pore Maturation. Issue 9 (15th May 2022) - Scott, Harry; Huang, Wei; Andra, Kiran; Mamillapalli, Sireesha; Gonti, Srinivas; Day, Alexander; Zhang, Kaiming; Mehzabeen, Nurjahan; Battaile, Kevin P.; Raju, Anjali; Lovell, Scott; Bann, James G.; et al.
Graphical abstract: Highlights: Anthrax protective antigen (PA) assembles into oligomeric prepores. PA prepores mature to conformationally distinct pores upon acidification. D425A PA mutation stalls pH-induced pore maturation at an intermediate state. D425A intermediate complex shares features of wild type prepore and pore. pH-induced changes of PA pore maturation are asymmetric. Abstract: The tripartite protein complex produced by anthrax bacteria ( Bacillus anthracis ) is a member of the AB family of β-barrel pore-forming toxins. The protective antigen (PA) component forms an oligomeric prepore that assembles on the host cell surface and serves as a scaffold for binding of lethal and edema factors. Following endocytosis, the acidic environment of the late endosome triggers a pH-induced conformational rearrangement to promote maturation of the PA prepore to a functional, membrane spanning pore that facilitates delivery of lethal and edema factors to the cytosol of the infected host. Here, we show that the dominant-negative D425A mutant of PA stalls anthrax pore maturation in an intermediate state at acidic pH. Our 2.7 Å cryo-EM structure of the intermediate state reveals structural rearrangements that involve constriction of the oligomeric pore combined with an intramolecular dissociation of the pore-forming module. In addition to defining the early stages of anthrax pore maturation, the structure identifies asymmetric conformational changes in the oligomeric pore that are influenced by the precise configuration of adjacent protomers.